The potential role of leptin in tumor invasion and metastasis - Ray, Amitabha; Cleary, Margot P. (Cytokine & growth factor reviews, 2017)
Red: Tumor-promoting effect. Blue: Dual role (tumor–suppressor or −promoting effect depending on the situation). CAFs: Cancer-associated fibroblasts, CTGF: Connective tissue growth factor, EGFR: Epidermal growth factor receptor, EMT: Epithelial–mesenchymal transition, ERK1/2: Extracellular signal-regulated kinases 1 and 2, HER2: Human epidermal growth factor receptor 2, HIF-1α: Hypoxia-inducible factor-1 alpha, IGF-I: Insulin-like growth factor-I, JAK2: Janus kinase 2, MMPs: Matrix metalloproteinases, NF-κB: Nuclear factor-kappa B, Ob-R: Leptin receptor, PI3K: Phosphatidylinositol 3-kinase, STAT3: Signal transducer and activator of transcription 3, TAMs: Tumor-associated macrophages, TGF-β: Transforming growth factor-beta, VEGF: Vascular endothelial growth factor. [Display omitted] •In the tumor microenvironment leptin impacts intracellular signaling which may accelerate cancer cell migration and metastasis.•Leptin plays a role in cancers of the digestive and reproductive systems, which are a major burden of neoplastic disease worldwide.•Elevated serum leptin affects the prognosis of both adenocarcinomas and squamous cell carcinomas.•Several cancer dissemination mechanisms have been documented to be linked with leptin. The adipocyte-released hormone-like cytokine/adipokine leptin behaves differently in obesity compared to its functions in the normal healthy state. In obese individuals, elevated leptin levels act as a pro-inflammatory adipokine and are associated with certain types of cancers. Further, a growing body of evidence suggests that higher circulating leptin concentrations and/or elevated expression of leptin receptors (Ob-R) in tumors may be poor prognostic factors. Although the underlying pathological mechanisms of leptin’s association with poor prognosis are not clear, leptin can impact the tumor microenvironment in several ways. For example, leptin is associated with a number of biological components that could lead to tumor cell invasion and distant metastasis. This includes interactions with carcinoma-associated fibroblasts, tumor promoting effects of infiltrating macrophages, activation of matrix metalloproteinases, transforming growth factor-β signaling, etc. Recent studies also have shown that leptin plays a role in the epithelial-mesenchymal transition, an important phenomenon for cancer cell migration and/or metastasis. Furthermore, leptin's potentiating effects on insulin-like growth factor-I, epidermal growth factor receptor and HER2/neu have been reported. Regarding unfavorable prognosis, leptin has been shown to influence both adenocarcinomas and squamous cell carcinomas. Features of poor prognosis such as tumor invasion, lymph node involvement and distant metastasis have been recorded in several cancer types with higher levels of leptin and/or Ob-R. This review will describe the current scenario in a precise manner. In general, obesity indicates poor prognosis in cancer patients.